Simplified Damper Cage Circuital Model and Fast Analytical–Numerical Approach for the Analysis of Synchronous Generators - Nuzzo, Stefano; Bolognesi, Paolo; Gerada, Chris; Galea, Michael (IEEE Transactions on Industrial Electronics, 2019)
The long and enduring history of utilization of the wound-field synchronous generator in a large number of applications makes it one of the most known and consolidated electrical machine technologies. Thus, its design, modeling, and analysis processes have been widely exploited and implemented through various and different methods, including the equivalent circuit approach. When a damper cage is embedded within the rotor of the synchronous generator, its theoretical analysis becomes quite complicated. Thus, today numerical tools are being used. In this paper, an alternative way of modeling symmetric damper cages of salient-pole synchronous generators is presented. The proposed approach is embedded in the circuital model of the generator. A hybrid analytical-numerical model is implemented, permitting to accurately predict the voltage waveforms of the generator with excellent accuracy, however, at a lower cost of computational resources than the pure numerical method. A case study of an off-the-shelf 400 kVA machine is considered to develop and validate the proposed technique. The results are compared with the corresponding finite-element and experimental evaluations for validation purposes.
Keywords: Control and Systems Engineering; Electrical and Electronic Engineering